Allegorizing History The Venerable Bede, Figural Exegesis and Historical Theory. - Furry, Timothy J. (Havertown : James Clarke & Co, 2014)
What is history? This question can be taken in many ways, including radically skeptical ones, but in 'Allegorizing History' Timothy J. Furry asks the questions not with that axe to grind but because it has become clear to him, through study of Bede and other ancient Christians, that history is not so simple. To be sure, many, if not all scholars, know that thanks to the work of postmodern philosophers and twentieth-century historical theorists like R.G. Collingwood, Hans-Georg Gadamer, and Hayden White. In this work, Furry shows that there are competing notions and purposes of historical pract.
Front cover; Title page; Dedication; Copyright; Contents; List of Images; Acknowledgments; Introduction; 1. (Re)Framing History: A Contemporary Historiography of Bede's 'Historia'; 2. Can History Be Figural? A Study of Bede's 'Historia Ecclesiastica' and 'De Templo'; 3. Interpreting Genesis: Creation and the Relationship between the Literal and Figural Senses; 4. Anachronism and the Status of the Past in Bede's 'Historia' and Figural Exegesis; 5. Bede and Frank Ankersmit: The Inevitability of Figural History; Conclusion; Bibliography; Back cover
Description based upon print version of record.
Keywords: Bede, -- the Venerable, Saint, -- 673-735 -- Criticism and interpretation; Historiography; History -- Religious aspects -- Christianity; HISTORY / Study & Teaching; Electronic books